The Use of Pictorial Analogy to Increase Students Achievement and Its Retention of Physics Lessons of Direct Current - Tomo Djudin; Selvaraj Grapragasem (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2019)
Analogy is considered a helpful way to help students visualize abstract concepts and assimilate new knowledge to an existing structure of cognitive. This study examines the effectiveness of the teaching with pictorial analogy models on students achievement and its retention of Direct Current lesson. A quasi-experimental method with one group pretest and (immediate and delayed) posttest design was employed in this study. The subjects consisted of 35 twelfth-grade students of public senior school in Pontianak City enrolled in the first semester of academic year 2017/2018; they were determined by using intact group random sampling technique. The student participants received instructions of the three pictorial analogy models. A parallel pretest-posttest of achievement test consisted of 10 items of factual knowledge, 10 items of conceptual knowledge, and 3 items of procedural knowledge. The operationalization of the pictorial analogies in this study referred to Glynns syntaxes. Data analysis found that: (1) the increasing of factual knowledge is 30.2 % in immediate posttest and 21.6 % in delayed posttest; (2)the students have promoted a significant conceptual change ( = 54.28, p < 0.05); and (3) there is a significant difference between the immediate posttest and pretest in terms of procedural knowledge (t = 4.02; p < 0.05) with the ES index is 4.78. It is concluded that the use of pictorial analogy models is effective (in high category) to increase students achievement of Direct Current lesson and the emergence of their retention is significant partially and simultaneously. In using pictorial analogies, teachers are encouraged to consider many similar features with the target concepts.